Allergic rhinitis causes loss of smell in children: The OLFAPEDRIAL study. Issue 8 (27th September 2016) - Langdon, Cristóbal; Guilemany, José María; Valls, Meritxell; Alobid, Isam; Bartra, Joan; Dávila, Ignacio; del Cuvillo, Alfonso; Ferrer, Marta; Jáuregui, Ignacio; Montoro, Javier; Sastre, Joaquín; Valero, Antonio; et al.
Abstract: Background: The objective of the OLFAPEDRIAL study was to assess the olfactory dysfunction in allergic paediatric population, which has been scarcely studied. Methods: Observational, cross‐sectional and multicentre study evaluated the sense of smell in untreated allergic rhinitis (AR) paediatric patients aged 6–12 years. Results: Forty‐four per cent (551 of 1260) of children with AR reported smell dysfunction, with both loss of smell frequency (52.1%, p < 0.001) and intensity (0.75 ± 0.84, p < 0.0001) being more frequent in patients with persistent than intermittent AR (38.0% and 0.51 ± 0.73, respectively). In addition, both loss of smell frequency and intensity increased according to disease severity (m‐ARIA classification) but always being significantly higher in persistent (p < 0.0001) than in intermittent AR. Conclusions: Children with allergic rhinitis present a mild–moderate loss of smell frequency and intensity which is clearly related to the disease duration and severity. The loss of smell can be considered, as in adults, a clinical marker of disease severity. Abstract :